2018
DOI: 10.26226/morressier.5b31ec6e2afeeb001345a3b8
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Hyperammonemia alters membrane expression of GluA1 and GluA2 subunits of ampa receptors in hippocampus by enhancing activation of the il-1 receptor: underlying mechanisms

Abstract: Background: Hyperammonemic rats reproduce the cognitive alterations of patients with hepatic encephalopathy, including altered spatial memory, attributed to altered membrane expression of AMPA receptor subunits in hippocampus. Neuroinflammation mediates these cognitive alterations. We hypothesized that hyperammonemia-induced increase in IL-1β in hippocampus would be responsible for the altered GluA1 and GluA2 membrane expression. The aims of this work were to (1) assess if increased IL-1β levels and activation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(18 citation statements)
references
References 42 publications
1
16
1
Order By: Relevance
“…74 Increased Src activity in the hippocampus of hyperammonaemic rats also activated PKCδ, which enhanced phosphorylation of GluN2B at Ser1303, reduced membrane expression of CaMKII and phosphorylation of GluA1 at Ser831, which reduced membrane expression of GluA1. 74 This report clearly showed the mechanisms by which neuroinflammation, through increased IL-1β content and activation of its receptor, altered the membrane surface expression of the subunits of AMPA receptors, which was responsible for impaired spatial learning and memory. This work identified two pathways by which neuroinflammation altered glutamatergic neurotransmission in the hippocampus.…”
Section: Modulation Of Neurotransmission and Spatial Learning And Mmentioning
confidence: 99%
See 2 more Smart Citations
“…74 Increased Src activity in the hippocampus of hyperammonaemic rats also activated PKCδ, which enhanced phosphorylation of GluN2B at Ser1303, reduced membrane expression of CaMKII and phosphorylation of GluA1 at Ser831, which reduced membrane expression of GluA1. 74 This report clearly showed the mechanisms by which neuroinflammation, through increased IL-1β content and activation of its receptor, altered the membrane surface expression of the subunits of AMPA receptors, which was responsible for impaired spatial learning and memory. This work identified two pathways by which neuroinflammation altered glutamatergic neurotransmission in the hippocampus.…”
Section: Modulation Of Neurotransmission and Spatial Learning And Mmentioning
confidence: 99%
“…AMPA receptors are key in the modulation of spatial learning and memory [67][68][69] and it has been reported that IL-1β could alter membrane expression 70 and cognitive function. [71][72][73] Taking this into account, Taoro-Gonzalez et al 74 proposed that, in hyperammonaemic rats, increased IL-1β levels in the hippocampus would activate their receptors and associated signal transduction pathways, which would alter GluA1 and GluA2 membrane surface expression. They showed that blocking the IL-1 receptor with the endogenous antagonist IL-1Ra reversed the alterations in membrane surface expression of AMPA receptor subunits in hippocampal slices from rats with 4-5 weeks of chronic hyperammonaemia.…”
Section: Modulation Of Neurotransmission and Spatial Learning And Mmentioning
confidence: 99%
See 1 more Smart Citation
“…Male Wistar rats (120-140 g; Charles River Laboratories, Wilmington, MA, USA) were made hyperammonemic by feeding them an ammonium-enriched diet as established by Felipo et al (38) with the modification introduced by Taoro-González et al (22). The experiments were approved by the Comité deÉtica de Experimentación Animal (Prince Felipe Research Center, Ministry of Agriculture, Valencia, Spain) and performed in accordance with the European Communities Council Directive (86/609/EEC).…”
Section: Animals and Model Of Chronic Hyperammonemiamentioning
confidence: 99%
“…IL-1b, a proinflammatory cytokine, acts as a neuromodulator in the healthy CNS. However, chronic low-grade elevation of IL-1b levels in the hippocampus (and other brain regions) is primarily involved in the pathogenesis of neurologic and psychiatric disorders, such as stroke, epilepsy, Parkinson's disease, Alzheimer's disease, or HE (19)(20)(21)(22).…”
mentioning
confidence: 99%